2022
DOI: 10.1002/dta.3372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urinary mercapturic acid excretions in users of various tobacco/nicotine products

Abstract: Urinary mercapturic acids (MAs) are detoxification products for electrophiles occurring in the human body. They are suitable biomarkers of exposure to directly acting electrophilic chemicals or to chemicals which generate the electrophile during its metabolism. We determined the urinary excretion of 19 MAs in habitual users of combustible cigarettes (CCs), electronic cigarettes (ECs), heated tobacco products (HTPs), oral tobacco (OT), and nicotine replacement therapy (NRT) products, and nonusers (NUs) of any t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 90 publications
(385 reference statements)
0
12
0
Order By: Relevance
“…The study protocol for the second study, as described in the original review [11], detailed a controlled, single-center study involving 60 healthy subjects, divided into six product use groups (five nicotine product user groups and one non-user group) based on the sole use of their products of choice (cigarettes, HTPs, EVPs, oral tobacco products, and oral/transdermal nicotine replacement therapy (NRT) products) [114]. The results of the study have been published in several articles, with each article looking at different biomarker classes [115][116][117][118][119][120][121]. The subjects were confined in a clinical setting for a period of 76 hours, during which time unrestricted use of their product of choice was permitted as described (cigarettes, HTPs, EVPs, oral tobacco products, and oral/transdermal nicotine replacement therapy products).…”
Section: Forced Switching Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol for the second study, as described in the original review [11], detailed a controlled, single-center study involving 60 healthy subjects, divided into six product use groups (five nicotine product user groups and one non-user group) based on the sole use of their products of choice (cigarettes, HTPs, EVPs, oral tobacco products, and oral/transdermal nicotine replacement therapy (NRT) products) [114]. The results of the study have been published in several articles, with each article looking at different biomarker classes [115][116][117][118][119][120][121]. The subjects were confined in a clinical setting for a period of 76 hours, during which time unrestricted use of their product of choice was permitted as described (cigarettes, HTPs, EVPs, oral tobacco products, and oral/transdermal nicotine replacement therapy products).…”
Section: Forced Switching Studiesmentioning
confidence: 99%
“…The exposure of HTP users to tobacco-specific nitrosamines (TSNAs), minor alkaloids, polycyclic aromatic hydrocarbons (PAHs), aromatic amines, ethylene oxide, 1,3-butadiene, and benzene was reported to be at levels comparable to those observed for non-users [116][117][118][119][120]. Overall, the authors concluded that unique differentiation between product use groups by means of a single biomarker was not possible for users of oral tobacco products, HTP users, and nicotine gum users [121].…”
Section: Forced Switching Studiesmentioning
confidence: 99%
“…NGPs deliver similar or somewhat reduced amounts of nicotine (19), but signi cantly lower amounts of toxicants (1,20). Use of NGPs was shown to be implicated with substantial reductions in the exposure to all classes of toxicants including aldehydes, epoxides, tobacco-speci c nitrosamines (TSNAs), polycyclic aromatic hydrocarbons (PAHs), aromatic amines compared to smokers of CCs by measuring suitable biomarkers of exposure (21)(22)(23)(24) (for review, see: (20,(25)(26)(27)(28)).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the considerable reduction (80-95%) in the exposure to tobacco combustion chemicals, use of NGPs involves the daily exposure to nicotine, matrix components and avor compounds in larger amounts and some toxicants more likely in trance amounts (microgram to nanogram range (20)). A systematic biomarker of exposure (BOE) study under controlled conditions with users of CCs, ECs, HTPs, oral tobacco (OT) and nicotine gum in comparison to non-users (NU) revealed that OT users (various products, not only snus) showed elevations in the exposure to TSNAs lower or close to that in CC smokers (21)(22)(23)(24). There was some weak evidence that HTP users' exposure to acrolein, acrylamide, acrylonitrile, o-toluidine and TSNA was slightly (but not signi cantly) higher than that of NU and the other non-CC groups, but much lower than that of smokers (CC).…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that this model can be used to screen for optimal pharmacokinetic properties of nicotine delivery systems. Scherer et al 7 describe some of their research to differentiate between users of different types of tobacco and nicotine products. They compared the urinary excretions of 19 different mercapturic acids (MAs; which serve as Biomarkers of Exposure to certain tobacco smoke toxicants) in six groups of volunteers who were exclusively using: combustible cigarettes; e‐cigarettes, heated tobacco products; oral tobacco products (predominantly snus); or nicotine replacement therapy (NRT; primarily nicotine gum); plus a group who did not use any tobacco or nicotine products.…”
mentioning
confidence: 99%